Kosovo tradition as an incentive to a stable identity – an impartial viewpoint - Marković, Saša M.; Zobenica, Adela J. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The epilogue to the story of Kosovo, which is drawn from the folktales of the Battle of Kosovo, is as much an inspiration and obsession as is the story’s prologue and central idea. Despite certain opinions, the potential of this story remains intact and untapped. Our opinion remains that the identity of Serbs needs to recognize the values of the heritage of Kosovo, and to apply it steadily and responsibly to a given historical moment. Any extreme attempts at politicizing people’s opinions on the fairness and the sacrifice, both through stereotypes and denials, imply our inconsistency and the inconsistency of our contemporaries, predecessors, or future generations. Our immaturity and failure to recognize our own heritage in the message that elevates us to humility and virtue is our experience only. The story of Kosovo will endure even if we, convinced that we are on the right path, fail to find it.